STRATEGI PUBLIC RELATIONS MEMPERTAHANKAN CITRA POSITIF: (STUDY KASUS PADA FADJAR STUDIOS PEMBUATAN STEMPEL DI SURAKARTA) - Dwiki Kurniawan, David; Suryo, Herning; Sihabuddin, Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Fadjar Studios is a facilities management service. The main objective of business efforts in carrying out a strategy to maintain a positive image is by carrying out programs to achieve company performance where Fadjar Studios by making updates which we distribute directly or through online media in order to get a positive image from the public. Based on these problems, there is a statement, namely: What is the public relations strategy for maintaining a positive image of Fadjar Studios, as well as steps fordata collection, planning, action and communication, and evaluation. The research approach used is a qualitative approach, because researchers want to know the strategies carried out by Fadjar Studios public relations in maintaining the company's image. The data collection techniques used in this research were observation, interviews and documentation. The theory used is the public relations theory of Cutlip, Center, and Broom (2005: 268). This theory explains the four steps of the public relations management process, namely: Data Collection, Planning, Communication, and Evaluation. The research results show that in maintaining a positive image, Fadjar Studios carries out a process of defining problems using data and information. The planning process uses systematic planning. The implementation process is carried out according to the plan that has been prepared. The evaluation process is carried out after implementation is complete. From this research it can be concluded that public relations implements strategies to maintain a positive image. The steps taken are also in accordance with applicable procedures Keywords: Strategy, Public Relations, Image, Fadjar Studios